Prevalence of Hyperglycemia and Hypoglycemia among Adult Inpatients at a University Hospital in Saudi Arabia - Khalid Z. Alshali,; Rami Ahmad,; Zuhair S. Al-Ghamdi,; Hisham Ismail,; Dima Joharji, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The objective of the study is to estimate the prevalence of hyperglycemia and hypoglycemia in adult inpatients and to evaluate the use of insulin sliding scale in preventing hyperglycemia and hypoglycemia. A cross-sectional study was performed between May 1- 7, 2012 on adult inpatients at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, documenting the patients' blood glucose values and the method of blood glucose management. Data were collected and analyzed using the Statistical Package for Social Sciences and Excel. Of the 280 included inpatients, the overall prevalence of diabetes and hyperglycemia was 39.3%. For patients with type 1 diabetes, the prevalence of severe hyperglycemia was 38.5% versus 17.6% in those with type 2 diabetes (P-value = 0.0001). Hypoglycemia was more prevalent among patients with type 1 diabetes (38.5%) compared to patients with type 2 diabetes (14.1%) (P-value = 0.0001). The type of insulin regimen used did not significantly affect the prevalence of hyperglycemia or hypoglycemia. The high prevalence of hyperglycemia and hypoglycemia among adult inpatients with diabetes and hyperglycemia indicates poor control of blood glucose levels, suggesting an urgent need to review the methods used in controlling blood glucose levels in inpatients at King Abdulaziz University Hospital.